THE BACKPACKER UMRAH PHENOMENON IN THE DIGITAL ERA: IMPACT ON PILGRIMS' SPIRITUALITY AND THE TRAVEL INDUSTRY - Kahfi, Al; Emi Puspita Dewi; Mohamed Esse Mohamoud (Multazam : Jurnal Manajemen Haji dan Umrah, 2025)
This study aims to analyze the phenomenon of backpacker umrah, which has gained popularity in the digital era, focusing on its opportunities, challenges, and impact on pilgrims' spirituality and the umrah travel business. Backpacker umrah allows pilgrims to organize their journeys independently using digital technology, such as ticket booking applications, accommodations, and worship information platforms. Employing a qualitative approach based on interviews and literature studies, the results indicate that umrah travel agencies can capitalize on these opportunities by developing strategies such as customized digital services, collaboration with backpacker communities, and offering more flexible umrah packages. Additionally, the study finds that technology has a dual impact on pilgrims' spirituality. On one hand, technology facilitates the implementation of worship; on the other hand, excessive reliance on technology can diminish the solemnity and spiritual meaning of the rituals. Therefore, it is crucial for pilgrims to maintain a balance between technology use and the essence of worship. This study provides valuable insights for the umrah travel industry in adapting to digital transformation while strengthening the spiritual dimensions of worship in the modern era.